Deskripsi Pola Asuh Orang Tua pada Anak Usia Dini Kelompok B di TK Cerdas Molibagu Desa Molibagu Kecamatan Bolaang Uki Kabupaten Bolaang Mongondow Selatan - Besse Salsa Maulina; Pupung Puspa Ardini; Rapi Us. Djuko (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
Parenting style refers to the methods parents use to educate, guide, discipline, interact with, and protect their children to help them mature within the norms of the family and society. This study aims to describe the parenting style of parents of aerly childhood children at TK Cerdas Molibagu Kindergarten, Molibagu Village, Bolaang Uki District, South Bolaang Mongondow Regency. The qualitative research employed a descriptive qualitative approach. Data were collected through observation and questionnaires. The findings showed that, based on observations and open-ended questionnaires from 11 respondents, 36% (4 out of 11) of parents implemented an authoritarian parenting style characterized by full parental control and strict rules with punishments for violations. Similarly, 36% (4 out of 11) of parents adopted a democratic parenting style, emphasizing two-way communication and mutually agreed-upon rules. Meanwhile, 27% (3 out of 11) employed a permissive parenting style, granting full freedom to the child, where decisions were primarily based on the child’s preferences. The result indicate that the dominant parenting styles applied by parents at TK Cerdas Molibagu are authoritarian and democratic.